CROSS-LINGUISTIC COMPARISON IN LANGUAGE ACQUISITION - Ahmedova Nodira Djavadullaeva (Modern American Journals, 2025)
This article explores the influence of cross-linguistic comparison on language acquisition of children, particularly who are brought up in a bilingual family. The models, both positive and negative sides of cross-linguistics comparison are given and discussed. Research also shows that children's rates of grammatical development and comprehension can vary significantly across different languages.